Level of Acceptability of Turmeric Ice Cream (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Ice cream is loved by most children and young teens, especially when the weather is hot because ice cream helps lower the body temperature. Ice cream is a sweetened or flavored frozen food that is typically eaten as a snack or dessert. To add a twist to ice cream, the researchers used turmeric as the flavor to give a unique and enticing taste to the customers. Turmeric (Curcuma longa) is a flowering plant from the ginger family, Zingiberaceae. The roots of turmeric are used for cooking and used as a spice for specific foods. The main purpose of this study was to know the level of acceptability of turmeric as the main ingredient in ice cream to the selected respondents in Home Economic Strand and determine whether a spice is acceptable as the main ingredient in ice cream. The researchers used the descriptive method of research to determine the prevailing conditions affecting a given group. The researchers used a simple random technique. To gather the information of 50 respondents, the researchers used survey questionnaires. The result of this study revealed the level of acceptability of turmeric ice cream in terms of the cited four variables. The taste of turmeric ice cream is good, delicious, and has a well-blended flavor. It also has a unique flavor because of turmeric. In terms of aroma, the strong smell of turmeric affects the acceptability of turmeric ice cream. In terms of nutritional value, turmeric ice cream has health benefits because turmeric is usually used as a flavoring agent and especially its most active compound called “curcumin,” which has many scientifically-proven health benefits. In terms of presentation, the product is well-presented and easy to handle. The packaging also enhances the aesthetic appeal of turmeric ice cream. The results showed that turmeric is acceptable among the two groups of respondents.
Keywords: acceptability, turmeric, ice cream